Antarctic Treaty: Report of the Norwegian antarctic inspection under article VII of the Antarctic Treaty ([Justis- og beredskapsdepartementet], 2001)
Article VII of the Antarctic Treaty entitles each Consultative Party to designate observers who shall have the right to carry out unannounced on-spot inspections. The purpose of these inspections is to promote the objectives of and ensure compliance with the provisions of the Antarctic Treaty and the easures adopted under it. The observers shall be accorded complete freedom of access at any time to all areas of Antarctica, including all stations within those areas, as well as vessels and aircrafts at points of embarkation and disembarkation. Article 14 of the Protocol on Environmental Protection to the Antarctic Treaty commit the Consultative Parties to undertake inspections under Article VII of the Antarctic Treaty in order to promote the protection of the Antarctic environment and dependent and associated ecosystems, and to ensure compliance with the Environmental Protocol.
Keywords: Antarktis; Norge; forskningsstasjoner

Research on Antarctic affairs at the FNI (Nansen news, 2001)
Keywords: Antarktis; forskning

Energetisk elektronnedbør over Antarktis - Åsnes, Arne (Universitetet i Bergen, 2001)
Keywords: Antarktis; fysikk

Trollbundet : en liten saga om en lang tur - Bø, Sindre (Commentum forl., 2001)
Keywords: Antarktis; polarekspedisjoner; polarområdene; reiser; reiseskildringer

Med hvalbåten "Silva" ved Syd-Shetland: om originaltegningen og opphavsmannen til jagebrua - Børresen, Dag Ingemar (Ambra : Sandefjordmuseene årbok, 2001)
Keywords: Sørishavet; hvalfangst; teknologi

Electron density variations in the upper D region at high latitudes according to in situ measurements - Danilov, Alexey; Smirnova, N.V.; Vanina-Dart, Liudmila; Blix, Tom Arild; Thrane, Eivind (Geomagnetism and Aeronomy, 2001)
A large set of rocket measurements of the electron concentration [e] in the upper D region at four rocket sites (Molodezhnaya (Antarctic), Heiss Island (Arctic), Syowa (Antarctic), and Andoya/Kiruna (Arctic)) is considered. The dependence of [e] on the solar zenith angle X and geomagnetic activity index ∑Kp is analyzed. It has been shown that, the spread in [e] values reaches two orders of magnitude at any assigned value of χ. Nevertheless, it is possible to draw a lower envelope for the entire set of points and to obtain the [e] variation with χ in undisturbed conditions. In an analysis of the envelopes, it is seen that a corpuscular ionization source (presumably, electrons with an energy of above 40 keV) exists in the nonsunlit D region even in quiet conditions. An analysis of the electron concentration dependence on the daily sum of ∑Kp indices (∑Kp) shows that, at all heights considered, increases [e] with increasing ∑Kp to a certain boundary value ∑Kp and then remains either constant (with a rather wide spread in the data) or even decreases. This saturation effect may be caused by the auroral oval equatorward motion. As a result of this motion the site position may change: it may move toward the boundary between the auroral oval and polar cap or even be within the latter. The slope k of the [e] variation plotted versus ∑Kp at different χ is considered. It is shown that k grows with increasing χ and is maximal at χ> 100°.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

A local geoid in Dronning Maud Land - The NARE 96/97 Geoid - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (IGeS Bulletin, 2001)
The main purpose of the present paper is to estimate the orthometric height of the Global Positioning System (GPS)-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m above sea level Troll has been connected to the Geodetic Infrastructure forAntarctica (GIANT)-network, but it’s orthometric height remains undetermined. A local geoid has been determined based on gravity-, tidal- and GPS-observations and available gravity anomalies. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta andTroll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE 1996/97; Troll forskningsstasjon; geodesi; kartlegging

Mumifiserte seler fra Dronning Maud Land, Antarktis - Gjertz, Ian; Wiig, Øystein (Fauna, 2001)
Keywords: Dronning Maud Land; dyr; seler; zoologi

Pesca: the history of Compañia Argentina de Pesca Sociedad Anónima of Buenos Aires: an account of the pioneer modern whaling and sealing company in the Antarctic - Hart, Ian B (Aidan Ellis, 2001)
Keywords: Antarktis; Carl Anton Larsen; fiskeindustri; hvalfangere; hvalfangst; hvalfangstindustri; hvalfangstnæring; hvalindustri; pelagisk; økonomi

A high-altitude snow chemistry record from Amundsenisen, Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn; Mayewski, Paul; Twickler, Mark; Whitlow, Sallie (Journal of Glaciology, 2001)
In this paper a detailed record of major ions from a 20 m deep firn core from Amundsenisen, western Dronning Maud Land, Antarctica, is presented. The core was drilled at 75° S, 2° E (2900 m a.s.l.) during austral summer 1991/92. The following ions were measured at 3 cm resolution: Na+, Mg2+, Ca2+, Cl−, NO3−, S04 2− and CH3SO3H (MSA). The core was dated back to 1865 using a combination of chemical records and volcanic reference horizons. The volcanic eruptions identified in this core are Mount Ngauruhoe, New Zealand (1974–75), Mount Agung, Indonesia (1963), Azul, Argentina (1932), and a broad peak that corresponds in time toTarawera, New Zealand (1886), Falcon Island, South Shetlands, Southern Ocean (1885), and Krakatau, Indonesia (1883). There are no trends in any of the ion records, but the annual to decadal changes are large. The mean concentrations of the measured ions are in agreement with those from other high-altitude cores from the Antarctic plateau. At this core site there may be a correspondence between peaks in the MSA record and major El Niño–Southern Oscillation events.
Keywords: Dronning Maud Land; fysisk geografi; glasiologi; iskjerner; kjemi; meteorologi

Klimavariasjoner gjennom de siste 45 000 14C år i Weddellhavet, Antarktis - Larsen, Anne Marit Løland (Universitetet i Bergen, 2001)
Keywords: Sørishavet; Weddellhavet; maringeologi; paleoklimatologi; sedimenter

Metal dynamics in an Antarctic food chain - Nygård, Torgeir; Lie, Elisabeth; Røv, Nils; Steinnes, Eiliv (Marine Pollution Bulletin, 2001)
The concentrations of copper, zinc, cadmium, selenium and mercury were determined in eggs, muscle, liver, kidney and stomach content of nestlings and adults of the Antarctic petrel, Thalassoica antarctica, and its predator, the south polar skua, Chataracta maccormicki, from Svarthamaren, Dronning Maud Land, Antarctica. The dominant food of the petrels is krill, Euphausia superba. The results show relatively high levels of cadmium in krill, which is assumed to be the main reason for the high levels of cadmium in petrels and skuas. Cadmium is almost absent in eggs, but accumulates very rapidly with age in nestlings. The copper concentrations in livers of nestling petrels reach very high levels during growth. This may be seen in connection with physiological development processes. Mercury seems to be accumulated with age and between trophic levels. Among the nestlings, the mercury levels decrease with increasing age, which may be accomplished by the excretion of mercury through the growth of feathers and as a dilution effect during growth. Selenium and mercury are inversely correlated in nestlings. The levels of zinc were similar for different nestling stages and between nestlings and adults in skuas and petrels.
Keywords: Dronning Maud Land; antarktispetrell; forurensning; fugler; krill; miljøgifter; næringskjede; ornitologi

Lichens of Antarctica and South Georgia : a guide to their identification and ecology - Øvstedal, Dag Olav; Smith, Ronald Lewis (Cambridge University Press, 2001)
Keywords: Antarktis; botanikk; lav; planter

Blue-ice areas in Antarctica derived from NOAA AVHRR satellite data - Winther, Jan-Gunnar; Jespersen, Martin Nørman; Liston, Glen E. (Journal of Glaciology, 2001)
We have mapped Antarctic blue-ice areas using the U.S. National Oceanic and Atmospheric Administration (NOAA) Advanced Very High Resolution Radiometer (AVHRR) Antarctica cloud-free image mosaic established by the United States Geological Survey. The mosaic consists of 38 scenes acquired from 1980 to 1994. Our results show that approximately 60 000 km2 of blue ice exist for each of the two main types of blue ice: “melt-induced” and “wind-induced”. Normally, the former type is located on slopes in coastal areas where climate conditions (i.e. persistent winds and temperature), together with favourable surface orientation, sustain conditions for surface and near surface melt. The latter blue-ice category occurs near mountains or on outlet glaciers, often at higher elevations, where persistent winds erode snow away year-round, and combined with sublimation creates areas of net ablation. Furthermore, we have identified an additional area of 121 000 km2 as having potential for blue ice. However, in these areas features such as mixed pixels, glazed snow surfaces, crevasses and/or shadows make interpretation more uncertain. In conclusion, a conservative estimate of Antarctic blue-ice area coverage by this method is found to be 120 000 km2 (∼0.8% of the Antarctic continent), with a potential maximum of 241 000 km2 (∼1.6% of the Antarctic continent).
Keywords: Antarktis; Dronning Maud Land; blåis; fjernmåling; glasiologi; satellite bilder; teknologi